THE ROLE OF BUSINESS CENTERS AND ENTREPRENEURSHIP HOUSES IN TRANSFORMING ENTREPRENEURIAL VALUES IN VOCATIONAL HIGH SCHOOL STUDENTS - Dyah Ayu Fitriastuti (Nusantara Economics and Entrepreneurships Journals, 2023)
Value transformation greatly affects how students absorb entrepreneurial values well and can implement them after graduating from school. Business Center and Entrepreneurship House is one of the places to transform entrepreneurial values through its programs. The purpose of this study is to identify the planning, program implementation, and program evaluation in the Business Center and Entrepreneurship House in transforming entrepreneurial values in students. Through descriptive qualitative research method with phenomenological approach. Techniques for collecting data are observation, interview, and documentation techniques. To test the validity of the data is done by triangulating data sources and triangulating techniques. The result of the research is the process of transforming entrepreneurial values in the Learners of SMK Darul Anwar is with the existence of activities such as those carried out by the Business Center and the Entrepreneurship House that greatly affect the entrepreneurial spirit of students. After participating in practical activities, students are motivated to become entrepreneurs in the future